Determinants of Long-Term Persistence with Tiotropium Bromide for Chronic Obstructive Pulmonary Disease. (4th May 2015) - Tanaka, Kyuto; Kamiishi, Nobufumi; Miyata, Jun; Kabata, Hiroki; Masaki, Katsunori; Ogura-Tomomatsu, Hiromi; Tomomatsu, Katsuyoshi; Suzuki, Yusuke; Fukunaga, Koichi; Sayama, Koichi; Betsuyaku, Tomoko; Asano, Koichiro
Abstract: Tiotropium bromide, a long-acting anticholinergic agent, improves pulmonary function and quality of life of patients suffering from chronic obstructive pulmonary disease (COPD). We retrospectively examined the factors that determine the long-term persistence with tiotropium bromide. Among 6, 301 patients who underwent pulmonary function tests in our pulmonary clinic between 2006 and 2009, 644 met the following criteria: 1) age > 40 years, 2) ≥ 20 pack-years smoking history, and 3) forced expiratory volume in 1 sec / forced vital capacity ratio < 0.7. The clinical information, including the prescription of tiotropium, was obtained from the patients' records. Tiotropium was administered to 255 patients (40%), of whom 48 (19%) discontinued treatment within 1 year, and 65 (25%) discontinued treatment within the median observation period of 32 months. The drug was discontinued because of ineffectiveness in 35 patients (73%), and because of adverse drug effects in 13 patients (27%). Young age, current smoking, absence of respiratory symptoms alleviation, and less severe disease characterized by a) mild airflow limitation, b) mild to moderate emphysema, or c) no exacerbation of COPD during the 1 st year of treatment were predictors of drug discontinuation.